Rural-Urban Migration and Agro-Technological Change in Post-Reform China - Kaufmann, Lena (Book collections on Project MUSE., 2021)
How do rural Chinese households deal with the conflicting pressures of migrating into cities to work as well as staying at home to preserve their fields? This is particularly challenging for rice farmers, because paddy fields have to be cultivated continuously to retain their soil quality and value. Drawing on ethnographic fieldwork and written sources, this book describes farming households' strategic solutions to this predicament. It shows how, in light of rural-urban migration and agro-technological change, they manage to sustain both migration and farming. It innovatively conceives rural households as part of a larger farming community of practice that spans both staying and migrating household members and their material world. Focusing on one exemplary resource - paddy fields - it argues that socio-technical resources are key factors in understanding migration flows and migrant-home relations. Overall, this book provides rare insights into the rural side of migration and farmers' knowledge and agency. Bron: Flaptekst, uitgeversinformatie.